Studi Deskriptif Persepsi Siswa Terhadap Layanan Orientasi Siswa Kelas X SMA Negeri 4 Yogyakarta - Sinta Budi Astuti (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2015)
This study aims to describe the students' perception of the orientation services of class X SMA Negeri 4 Yogyakarta. This research is descriptive quantitative. The participants consisted 104 students of 10th grade at SMA Negeri 4 Yogyakarta selected by random sampling techniques. The instruments used in data collection are questionnaires. The obtained data of the students' perception of orientation services were analyzed using simple calculation by categorizing them into three criteria: good, moderate, poor. The results of the research showed that the students’ perception of the orientation services of class X SMA Negeri 4 Yogyakarta are categorized as good, moderate, and poor, reaching the average percentage of each are 49%, 51%, and 0%, respectively. The results of this study can be used as consideration for the guidance and counseling teachers in developing orientation services in accordance with the students’ needs and interests